Clean Transport Network in Nigerian Environment: Climatic Issues and Way Forward - Oyebode, Oluwadare Joshua (Journal of Sustainability and Environmental Management, 2022)
There is dire need for adequate planning and digital innovations for developing clean transport networks in African urban communities for better climatic condition and sustainable green environment. This paper examines climatic actions and sustainability perspectives of clean transport network development in Nigeria. Methodology adopted included reconnaissance survey of transport facilities, literature survey, checking of available data and government policy on clean transport network in Nigeria. Other information was also obtained from interview of selected engineers and energy experts in transportation sectors. Finding revealed that there is need to improve on financial capacities and future investments in digital advancements for integrated solutions in infrastructural development, resilient communities and transportation facilities for environmental health and clean transport network. The transportation industry is crucial to meet climate change mitigation goals and the Sustainable Development Goals (SDGs). Because of the expanding demand for transportation from various economic sectors such as industry, energy, health, home, and commercial and other aspects, the demand for transportation is in increasing trend. All issues related to road construction, Public Private Partnerships, traffic management and contract adjudication in transport sector must be carefully resolved. The paper concluded that there is urgent need to strengthen the development of clean transport network in Nigerian environment especially on climate action and sustainability perspectives. The impact of sustainable applications of mobility cannot be over emphasized. Adequate engineering and sustainable green initiatives should be deployed for economic growth and clean transport network in Nigeria.